Recent trends and advancement in metal oxide nanoparticles for the degradation of dyes: synthesis, mechanism, types and its application - Senthil Rathi B.; Ewe L.S.; Sanjay S.; Sujatha S.; Yew W.K.; Baskaran R.; Tiong S.K. (Taylor and Francis Ltd., 2025)
Synthetic dyes play a crucial role in our daily lives, especially in clothing, leather accessories, and furniture manufacturing. Unfortunately, these potentially carcinogenic substances are significantly impacting our water systems due to their widespread use. Dyes from various sources pose a serious environmental threat owing to their persistence and toxicity. Regulations underscore the urgency in addressing this problem. In response to this challenge, metal oxide nanoparticles such as titanium dioxide (TiO2), zinc oxide (ZnO), and iron oxide (Fe3O4) have emerged as intriguing options for dye degradation due to their unique characteristics and production methods. This paper aims to explore the types of nanoparticles suitable for dye degradation, various synthesis methods, and the properties of nanoparticles. The study elaborates on the photocatalytic and adsorption-desorption activities of metal oxide nanoparticles, elucidating their role in dye degradation and their application potential. Factors influencing degradation, including nanoparticle properties and environmental conditions, are discussed. Furthermore, the paper provides relevant case studies, practical applications in water treatment, and effluent treatment specifically in the textile sector. Challenges such as agglomeration, toxicity concerns, and cost-effectiveness are acknowledged. Future advancements in nanomaterial synthesis, their integration with other materials, and their impact on environmental regulations are potential areas for development. In conclusion, metal oxide nanoparticles possess immense potential in reducing dye pollution, and further research and development are essential to define their role in long-term environmental management. ? 2024 The Author(s). Published by Informa UK Limited, trading as Taylor & Francis Group.